Verification of Design Equations for Brittle Failure Mode in Bolted Connections of Local Hardwoods. - Abdul Razak, Abdul Karim; Norazzlina, M.Sa’don; Muhammad Na'imullah, Kamarul Ash'ari; Nursahira, Ibrahim; Xavier Langit, Ujan (Universiti Malaysia Sarawak, 2018)
Due to the existing design equations of MS544: Part 5: 2001 are only considering a ductile failure mode, this study was initiated because many published experimental works had identified a brittle failure mode in timber joints. Because of this study was executed to provide a set of optimised design equations for retrofitting the unreinforced masonry buildings, the use of the current Malaysian Timber Standard, as it is now can cause inaccuracy in designing the connection capacity. A lack of experimental data to examine the effectiveness of the code in predicting the timber bolted connection strength, especially in local hardwoods, also motivates this present study to be conducted. From the results obtained, the use of the timber standard and other design equations was validated.